O conselho administrativo de recursos fiscais (CARF) : estrutura, funcionamento e importância na resolução de conflitos tributários federais - Monteiro, Eduardo Martins Neiva (2012)
It is up to the Conselho Administrativo de Recursos Fiscais (CARF) to appreciate, in second instance, the federal tributary administrative processes, the general objective of the research, after all, was that which gave it a descriptive character, the ability to know and detail the structure of how the adjudicative activity works. The CARF consists of a department in the Ministério da Fazenda, of a parity composition, integrated by representatives of the Fazenda Nacional and contributers, which resulted in the unification of the extinct Primeiro, Segundo e Terceiro Conselhos de Contribuintes and of the old Câmara Superior de Recursos Fiscais. Taking in consideration its institutional mission, of assuring the society the impartiality and celerity in the solution of litigious tributary , we tried to identify in its Internal Regiment the presence of norms which contribute to the concretization of the reasonable duration of the process, of which it was possible to extract an understanding of the Supremo Tribunal Federal after a constitutional positivization, and for the guarantee of impartial judgments. As a result, there are regimental norms visibly turned to the concretization of those fundamental rights. As to the impartiality, it does not relate to the parity composition model of the collegiate. The procedure for the selection of the representatives, which contributed to its concretization, and to the necessity of implementation of a kind of quarantine, as well as a reinforcement in the hypothesis of the impediment